Methods of instruction and the use of new technologies in translator training - Varela-Salinas, María José (My University, 2020)
In 2007, I examined some tools that could potentially prove useful in translator training. This article stated that in today's society, in which dizzying technological advances are taking place, new technologies have become essential tools and their mastery is a sine qua non for accessing many jobs. Therefore, despite the challenges they might pose, these tools are now requirements for teaching any subject. Translator training is no exception. Time has passed and, at the same time, experience has grown along with advances in the field of new technologies. Many tools which aim to help translators fulfill their tasks have been improved and expanded, such as the different translation memory suites or the corpus management programs. The purpose of this article is to broaden the debate on whether technology supports translator training and what its advantages and limits are, providing examples of the use of new technologies in translator training. It is not exhaustive, but it aims to highlight the diversity of possible applications through a pedagogical approach.
Este trabajo se realizó en el marco de la Cátedra Estratégica de Interactividad y Diseño de Experiencias.
Keywords: Traducción; Traductores; Translator training; Pedagogy; Assessment; New technologies; Learning styles; Learning theories